Implementation of Marriage Policy and Catin's Attitudes Regarding Marriage Counseling on the Performance of Suscatin Mentors in Realizing Family Marriage Adjustments - Asep Muzayin Aturmudi (Pasundan Social Science Development, 2023)
This research aims to investigate the impact of marriage policies and the attitudes of prospective brides and grooms towards marriage counseling on the performance of pre-marital counselors in achieving marital adjustments within Garut Regency. Employing an exploratory analysis method, the study focused on the leaders of the Marriage Advice, Development, and Preservation Agency in Garut Regency, including the Chairperson and Vice-Chairpersons, totaling 86 individuals, utilizing a census sampling technique. Data collection encompassed questionnaires, interviews, observations, and documentary research. Statistical path analysis was the chosen technique to address the research hypotheses. The primary hypothesis testing revealed that the implementation of marriage policies and the attitudes of prospective brides and grooms influenced pre-marital counselor performance in achieving adjustments by 12.79%, with the remaining 87.21% attributed to other factors. Further sub-hypothesis testing demonstrated that marriage policies and prospective brides' and grooms' attitudes toward marriage counseling accounted for 25.43%, while other factors constituted 74.57%. Intriguingly, the implementation of marriage policies and attitudes toward marriage counseling did not significantly impact marital adjustments (path coefficient of 0.0364). Pre-marital counselor performance also had limited effects on marital adjustments (path coefficient of 0.1526). Moreover, there was a positive correlation between the implementation of marriage policies and the attitudes of prospective brides and grooms toward marriage counseling (partial correlation coefficient of 0.6783). The research identified key issues, such as suboptimal policy implementation, lack of awareness and motivation among prospective brides and grooms, ineffective interagency collaboration, and a shortage of skilled staff among pre-marital counselors. In light of these findings, it is recommended to improve policy implementation, enhance interagency cooperation, and increase awareness among prospective brides and grooms regarding the significance of pre-marital counseling for successful marriages. These measures are essential for addressing the prevalent marital issues and lack of warmth and affection in young couples' family lives in Garut Regency.